Pengembangan potensi lokal ikan menjadi nugget dan abon ikan untuk meningkatkan kesejahteraan masyarakat dan menurunkan angka kejadian stunting di Kanigoro, Saptosari, Gunungkidul - Raden Roro Dewi Ngaisyah; Andre Kusuma Adiputra (Journal of Community Empowerment for Health, 2019)
Kanigoro Village is blessed abundantly with great potential for fish resources development. Its strategic location by the seashore also poses an opportunity for Kanigoro to become a center for local home-based culinary industries focusing on local fish, such as fish nuggets and floss (shredded meat), which are rich sources of animal protein. Despite the plentiful local protein sources, a high prevalence of stunting continues to plague Kanigoro Village, reaching up to 48.2%. Developing fish-based culinary industries may become a means to reduce the stunting rates as well as to improve the economic status of the villagers. This project aimed to develop the fish-based local food processing into nuggets and floss to improve family economies and nutritional status in Kanigoro Village through a community-based approach. It began with the sharing of the project plan to gain support from the community. The team collaborated with local Kanigoro organizations, namely posyandu cadres and women's group. The training was given to the women's group on marketing, such as providing nutritional information on the packages, developing attractive packaging, and introducing marketing niches. Posyandu cadres were trained to motivate the villagers to increase fish consumption. After the training, the groups conducted meetings with the local women under the supervision of the team. In the meeting sessions, they encouraged villagers to eat more fish. Through the training, the local women acquired new knowledge on product enhancement, starting from improved processing hygiene, upgraded packaging, provision of nutritional information, and innovative marketing ventures. In the gatherings, posyandu cadres were able to deliver motivation to augment fish consumption. They could measure the height and weight of children under five correctly, enabling them to identify children with stunting. The knowledge and skills acquired from this project will equip the local villagers to prevent and reduce stunting prevalence in Kanigoro Village.